RELATIONSHIP BETWEEN SCIENCE PROCESS SKILLS TEACHING APPROACH AND LEARNING OUTCOMES IN BIOLOGY IN SECONDARY SCHOOLS IN MAKUENI COUNTY, KENYA - NDOLO, FRANCIS KASEKE (MksU Press, 2023)
Biology makes students aware of the nature of their daily life, and the care and protection of the environment. This study looked at the relationship between Science Process Skills Teaching Approach and learning outcomes in biology in secondary schools in Makueni County, Kenya. The persistently low level of students’ learning outcomes in biology, observed for a long time prompted this research. The teaching of the abstract nature of biological concepts had remained teacher-centered with the learner being a passive participant with minimum learning resource interaction. The objectives of the study were: To determine the difference in learners’ self-efficacy in biology among students taught by Science Process Skills Teaching Approach and those taught using Conventional Teaching Methods; To establish the difference in learners’ creativity in biology of students taught using Science Process Skills Teaching Approach and Conventional Teaching Methods; To establish the difference in the level of critical thinking for students exposed to Science Process Skills Teaching Approach and Conventional Teaching Methods; To determine the difference in learners’ academic performance in biology among students exposed to Science Process Skills Teaching Approach and Conventional Teaching Methods. The constructivism and experiential learning theories guided the study. It adopted a mixed research methodology that had both qualitative and quantitative and a Quasi-Experimental Research Design that involves Solomon's Four Non-Equivalent Control Group Design. The accessible population was Form Two Biology students within Makueni County. The study used a stratified random sampling technique to assign the four public co-educational secondary schools from the randomly sampled four Sub-Counties in which only one school per the sampled Sub-County was to participate in the study. The research selected a sample size of 204 Form Two students from the county. SPSTA was the intervention for the two experimental groups and Conventional Teaching Methods were for the control groups. A five-point Likert scale questionnaire measured the students’ achievement in self-efficacy in biology while Biology Assessment Test (BAT) measured the students’ learning outcomes in creativity, critical thinking, and academic performance. Research experts from the department of educational communication and technology of Machakos University and two experienced biology teachers did content and construct validation of the instruments. The reliability test used the split-half reliability through the KR-20 formula for the BAT, resulting to a coefficient of α= 0.860, and the five-point Likert scale questionnaire used Cronbach’s alpha which gave a coefficient of α=0.870. The study used Statistical Package of Social Sciences (SPSS) version 21.0 to analyze the collected data. The expression of the students’ self-efficacy levels was in terms of percentage of their confidence levels. Data analysis used descriptive and inferential statistics. Descriptive statistics calculated mean scores, and standard deviations while inferential calculated t-test, One-Way ANOVA, ANCOVA, Least Significant Difference (LSD) Post-Hoc Scheffe Multiple Comparisons, and Chi-Square Tests to test the hypothesis at α 0.05 level of confidence. The findings of the study demonstrated that SPSTA enhances learning outcomes in students’ self-efficacy in biology, creativity, critical thinking, and academic performance. The results of the study will provide useful information to biology teachers, curriculum developers, Quality Assurance and standards officers (QASO), and teacher-trainers.